Initial outcomes of a single-institution hepatic artery infusion pump program for colorectal liver metastases and intrahepatic cholangiocarcinoma: Safety, feasibility, and circulating tumor DNA tracking - Ocuin, Lee M.; Stitzel, Henry; Chung, Michelle; Tirumani, Sree Harsha; Elshami, Mohamedraed; Tomaro, Maria; Miller-Ocuin, Jennifer L.; Deitz, David W.; Steinhagen, Emily; Charles, Ronald; Costedio, Meagan; Liu, Michael; et al. (Surgery, 2025)
Hepatic artery infusion with floxuridine is a treatment option for patients with colorectal liver metastases or intrahepatic cholangiocarcinoma. Outcomes from newer centers are understudied. Predictive markers are needed, and quantitative circulating tumor DNA is an emerging candidate method for predicting response in patients receiving hepatic artery infusion. We aimed to describe safety, feasibility, early oncologic outcomes, and quantitative circulating tumor DNA dynamics in patients treated with hepatic artery infusion at a newly established program. Single-institution analysis of patients who underwent hepatic artery infusion pump placement (April 2022–April 2024) was conducted. Primary outcomes included safety and feasibility (receiving ≥1 cycle of floxuridine). Secondary outcomes included radiographic response (Response Evaluation Criteria in Solid Tumors 1.1), relative dose intensity of floxuridine received, and quantitative circulating tumor DNA response. A total of 36 patients underwent hepatic artery infusion pump placement (colorectal liver metastases: 32; cholangiocarcinoma: 4). Technical success was 100%. Feasibility was 97%. One patient experienced mortality at 90 days from disease progression. Three patients (8%) experienced a total of 5 hepatic artery infusion pump-specific complications (pump pocket [n = 3], hemorrhage [n = 1], biliary sclerosis [n = 1]). Median relative dose intensity was 68.5% (colorectal liver metastases: 68.3%; cholangiocarcinoma 72.5.0%). For the 27 patients who underwent floxuridine therapy with available postoperative imaging, disease control rate was 97% (partial response: n = 15; stable disease: n = 11). Quantitative circulating tumor DNA was obtained from 16 patients (44%). Circulating tumor DNA dynamics appeared to correlate with and precede radiographic response. Implementation of a new hepatic artery infusion program is safe and feasible with promising early oncologic outcomes. Circulating tumor DNA tracking is achievable and dynamic changes in circulating tumor DNA may correlate with radiographic response to treatment.